The Indonesian-English Code-Mixing on Deddy Corbuzier’s YouTube Channel - Mulyajati, Enggar (Interference: Journal of Language, Literature, and Linguistics, 2023)
Abstract. Nowadays, it is common that bilingual speech occurs conversation, in this case Indonesian-English. The process of mixing languages is called code-mixing. The phenomena of code-mixing occured on Deddy Corbuzier's YouTube channel named Close the Door. This channel invites speakers with diverse educational, social, economic, and cultural backgrounds that cause the speakers mix languages in their speech. Thus, it is interesting to analyze the types of code-mixing and the reasons the speakers do code-mixing. This study aims to analyze and explain the types of code-mixing and the reasons for speakers to code-mix the utterances in the conversations in the podcast. This research uses descriptive qualitative method by analyzing the transcription of conversations on the podcast. Data was determined using purposive sampling technique. The results show that there are three types of code mix and five reasons for bilingual speakers to mix codes in their speech. Based on the results of this study, even though bilingual speakers speak spontaneously, it turns out that they have certain reasons when mixing speech in conversations. Keywords: English, Code-Mixing, YouTube, Deddy Corbuzier, Bilingualisme